Immorality
Set of 7 posters with photographs and text on racial discrimination and social conditions in South Africa in the early 1970s; four posters have added text (in Dutch) that these posters of the Christian Institute have been banned by the South African government. Vier posters met aanvullende tekst: "Het Direktoraat voor Publikaties van de Zuid-Afrikaanse regering heeft deze poster van het Christelijk Instituut verboden".